Woody clockworks: circadian regulation of night‐time water use in Eucalyptus globulus. Issue 3 (25th June 2013) - Resco de Dios, Víctor; Díaz‐Sierra, Rubén; Goulden, Michael L.; Barton, Craig V. M.; Boer, Matthias M.; Gessler, Arthur; Ferrio, Juan Pedro; Pfautsch, Sebastian; Tissue, David T.
Summary: The role of the circadian clock in controlling the metabolism of entire trees has seldom been considered. We tested whether the clock influences nocturnal whole‐tree water use. Whole‐tree chambers allowed the control of environmental variables (temperature, relative humidity). Night‐time stomatal conductance ( g s ) and sap flow ( Q ) were monitored in 6‐ to 8‐m‐tall Eucalyptus globulus trees during nights when environmental variables were kept constant, and also when conditions varied with time. Artificial neural networks were used to quantify the relative importance of circadian regulation of g s and Q . Under a constant environment, g s and Q declined from 0 to 6 h after dusk, but increased from 6 to 12 h after dusk. While the initial decline could be attributed to multiple processes, the subsequent increase is most consistent with circadian regulation of g s and Q . We conclude that endogenous regulation of g s is an important driver of night‐time Q under natural environmental variability. The proportion of nocturnal Q variation associated with circadian regulation (23–56%) was comparable to that attributed to vapor pressure deficit variation (25–58%). This study contributes to our understanding of the linkages between molecular and cellular processes related to circadian regulation, and whole‐tree processes related to ecosystem gas exchange in the field.